Efficient heat removal via thorny devil nanofiber, silver nanowire, and graphene nanotextured surfaces. (October 2016) - Yoon, Hyun; Kim, Min-woo; Kim, Hayong; Kim, Do-Yeon; An, Seongpil; Lee, Jong-Gun; Joshi, Bhavana N.; Jo, Hong Seok; Choi, Jeehoon; Al-Deyab, Salem S.; Yarin, Alexander L.; Yoon, Sam S.
Highlights: Several types of nano-textured surfaces were studied to enhance heat removal rate in a cooling device. The nano-textured surfaces copper-plated nanofibers, graphene oxide flakes, and silver nanowires. The effect of the macroscopic turbulizers on cooling was also investigated. The most significant cooling enhancement was achieved with silver nanowires. Abstract: Several types of nano-textured surfaces were studied with the goal to enhance heat removal rate in a cooling device (a heat sink) with water flow-through. The nano-textured surfaces where heat removal to flowing water took place included: (i) electrospun copper-plated thorny-devil nanofibers deposited on the copper substrate, (ii) graphene oxide flakes sprayed on the copper substrate, and (iii) silver nanowires spin-coated on a separate copper substrate. Their cooling performance was monitored by measuring the difference between the outlet and inlet temperature of water flowing through the heat sink and the temperature of the nano-textured copper substrate in the heat sink. The effect of the macroscopic vortex generator (wires) on cooling of the heat sink surface was less than that of the nano-textured surfaces, which revealed that the latter provide a much larger interfacial area, rather than an extra flow mixing, to enhance heat transfer rate. Of the nano-textured surfaces the most significant cooling enhancement was achieved with silver nanowires.